EFFECTIVENESS OF PROJECT-BASED LEARNING IN IMPROVING STUDENT COMMUNICATION SKILLS - Kusmiarti, Reni; Rustinar, Eli; Paulina, Yanti; Hasibuan, Anim (JURNAL EDUSCIENCE, 2025)
Purpose–Cultivating strong communication abilities is essential for navigating the challenges of today's workplace. These skills enhance academic performance and serve as a fundamental asset in meeting the demands of an ever-evolving and competitive job market. This study aims to evaluate the effectiveness of Project-Based Learning in enhancing the communication skills of communication science students.Methodology–The method used in this study was pre-experimental with a one-group pre-test and post-test design. The research subjects comprised 73 students from the Communication Studies Program, Muhammadiyah University of Bengkulu. Data was collected using pre-tests and post-tests to determine students' communication skills before and after being given learning treatment with the Project-Based Learning (PjBL) approach. The data analysis technique was carried out using a variable normality test and a hypothesis test to see the difference in the pre-test and post-test scores of communication skills, with a significance of 0.05.Findings–The research conclusion is that there is a significant difference between the results of the student pre-test and the post-test of student communication skills with a paired samples test (t) value of 12.848 with a p-value of 0.000. There is a difference between communication skills (pre-test) and communication skills (post-test). Statistical analysis shows that the variables in this study are typically distributed. The hypothesis test results show a t-value of 12.848, which is greater than the t-table of 1.666.Significance –The application of PjBL significantly contributes positively and effectively to improving students' communication skills. Therefore, educators should emphasize the Project-Based Learning (PjBL) approach in learning, which has been proven effective in improving students' communication skills.